2016
DOI: 10.1016/j.ajhg.2016.07.018
|View full text |Cite
|
Sign up to set email alerts
|

NAXE Mutations Disrupt the Cellular NAD(P)HX Repair System and Cause a Lethal Neurometabolic Disorder of Early Childhood

Abstract: To safeguard the cell from the accumulation of potentially harmful metabolic intermediates, specific repair mechanisms have evolved. APOA1BP, now renamed NAXE, encodes an epimerase essential in the cellular metabolite repair for NADHX and NADPHX. The enzyme catalyzes the epimerization of NAD(P)HX, thereby avoiding the accumulation of toxic metabolites. The clinical importance of the NAD(P)HX repair system has been unknown. Exome sequencing revealed pathogenic biallelic mutations in NAXE in children from four f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
111
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(130 citation statements)
references
References 19 publications
9
111
0
Order By: Relevance
“…A genome-wide meta-analysis identified APOA1BP (the gene encoding the AIBP protein) as a susceptibility locus for migraine (Anttila et al, 2013). A recent human study reports that APOA1BP variants leading to the loss of AIBP expression were found in a lethal neurometabolic disorder of early childhood (Kremer et al, 2016). Further studies are needed to explore the endogenous AIBP function.…”
Section: Discussionmentioning
confidence: 99%
“…A genome-wide meta-analysis identified APOA1BP (the gene encoding the AIBP protein) as a susceptibility locus for migraine (Anttila et al, 2013). A recent human study reports that APOA1BP variants leading to the loss of AIBP expression were found in a lethal neurometabolic disorder of early childhood (Kremer et al, 2016). Further studies are needed to explore the endogenous AIBP function.…”
Section: Discussionmentioning
confidence: 99%
“…WES on genomic DNA from affected individual P3 was performed at the Institute of Human Genetics (Munich, Germany) using the SureSelect Human All Exon 50 Mb kit (Agilent, Santa Clara, CA, USA) for in‐solution enrichment followed by sequencing as 75 bp paired‐end runs on a HiSeq2500 (Illumina) as described previously [Haack et al., ; Kremer et al., ]. This achieved an average of 143‐fold coverage with 97.7% of the exome covered at least 20‐fold.…”
Section: Methodsmentioning
confidence: 99%
“…5 In the absence of NAXE protein there is an increase in cyclic-NADHX that has been shown to inhibit cellular NADH dehydrogenases. 68 Two splice variants of AIBP are synthesized with the longer form predicted to reside in the mitochondria and the shorter form remaining in the cytosol. 7 As an indication of its importance mutations in the APOA1BP gene are associated with lethal neurometabolic disorders of childhood.…”
mentioning
confidence: 99%
“…7 As an indication of its importance mutations in the APOA1BP gene are associated with lethal neurometabolic disorders of childhood. 6, 9 There is controversy regarding whether AIBP is exclusively intracellular or secreted, with Ritter et al (2002) demonstrating its presence in urine, cerebrospinal fluid, and in the serum of some septic patients, but not in the serum of healthy patients. 10 HepG2 cells were also reported to secrete small amounts of AIBP.…”
mentioning
confidence: 99%